2007
DOI: 10.1007/s10653-006-9068-7
|View full text |Cite
|
Sign up to set email alerts
|

The Sagamu cement factory, SW Nigeria: Is the dust generated a potential health hazard?

Abstract: The aim of this study was to assess the heavy metal content of the dust generated by the Sagamu cement factory and its attendant health hazards on the immediate environment, especially on the inhabitants of the area. A total of 25 samples were collected and analyzed using inductively coupled plasma-optical emission spectrometry. Records of medical ailments associated with heavy metal toxicity were also compiled from the Obafemi Awolowo Teaching Hospital situated in the town. The results for some of the selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 1 publication
1
18
0
2
Order By: Relevance
“…A similar study (Morales et al 1996) suggested that atmospheric concentration of zinc and cadmium was higher in western Venezuelan savannah than expected, also due to emissions from a cement factory. A more dramatic situation was described in Nigeria (Abimbola et al 2007) where the high concentration of heavy metals was associated with human diseases. On the other hand, negligible effect of cement and cement dust was observed in rats ( van Berlo et al 2009).…”
Section: Generation Of Particlesmentioning
confidence: 99%
“…A similar study (Morales et al 1996) suggested that atmospheric concentration of zinc and cadmium was higher in western Venezuelan savannah than expected, also due to emissions from a cement factory. A more dramatic situation was described in Nigeria (Abimbola et al 2007) where the high concentration of heavy metals was associated with human diseases. On the other hand, negligible effect of cement and cement dust was observed in rats ( van Berlo et al 2009).…”
Section: Generation Of Particlesmentioning
confidence: 99%
“…Though, most elements are essential for proper functioning of the human biological system [4], humans are not adapted to deal with them at concentrations higher than the reference values that can be tolerated by the human homeostasis [2,3,5]. Cement factories have been a major source of heavy metals emission to the environment with several reports showing higher concentrations of heavy metals around cement factories [6][7][8]. The particulate matter that is emitted from quarrying of limestone to the final process of packaging of cement is deposited on the soil, vegetation and water bodies, which usually serve as drinking water sources in the environment, thus increasing the pollution quotient of the surrounding communities [9].…”
Section: Introductionmentioning
confidence: 99%
“…Cement factories have been reported as a major source of heavy metals emission into the environment with several reports showing higher concentrations of heavy metals in the vicinity of cement factories (5)(6)(7)(8)(9). Contamination of the environment with many pollutants is one of the most significant problems in this century.…”
Section: Introductionmentioning
confidence: 99%